Electron transfer from Geobacter sulfurreducens to mixed methanogens improved methane production with feedstock gases of H2 and CO2. (March 2022) - Dong, Haiquan; Cheng, Jun; Li, Hui; Yue, Liangchen; Xia, Rongxin; Zhou, Junhu
Graphical abstract: Highlights: A co-culture of G. sulfurreducens and methanogens was established. Optimizing inoculation volume ratio of G. sulfurreducens to mixed methanogens. CH4 yield close to the maximum theoretical yield of 0.25 mL/ml H2. Conversion efficiency of H2 to CH4 increased from 72 to 96% Abstract: In order to solve problems of poor utilization of H2 and CO2 in biomethane conversion with mixed methanogens due to multi-channel competition and nondirectional electron transfer, Geobacter sulfurreducens were cocultured with mixed methanogens to promote oriented metabolic pathway of H2 and CO2 to produce CH4 . When inoculation volume ratio of G. sulfurreducens to mixed methanogens was 2:4, CH4 yield increased to 0.24 mL/ml H2 (close to the maximum theoretical yield of 0.25 mL/ml H2 ) and conversion efficiency of H2 to CH4 increased from 72 to 96%. Electrochemical detection and three-dimensional fluorescence spectra showed that the co-culture system had an increased metabolic capacity and spectral intensity of fulvic acid-like compounds was enhanced, which mediated direct interspecific electron transfer to produce CH4 . The 16S rRNA gene sequencing showed that relative abundance of G. sulfurreducens and Methanoculleus increased, indicating an established syntrophic relationship between G. sulfurreducens and Methanoculleus .